1991
DOI: 10.1016/0014-5793(91)80484-k
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of two conserved sequence motifs in HIV‐1 reverse transcriptase

Abstract: Two tort,erred sequence motifs, oc~:urrin$ in HIV-I r~verse transeriptase~ at re,,dues II0+A 16 trod 183~190. have been studied ufinB ~ite.direeted mutall,,,tesis of the cloned llene. In particular, asp, flares at positioni 185 and 11t6 have each been rout;tied to either asparalline or glutamate, The resulting mutant proteins wer~ catalytically inactive but still able to bind th~ template.primer complex, ooly rA.oli~o tiT. Other mutations in these re|lions resulted in reduced reverse transcriptase activity but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
70
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 15 publications
9
70
0
Order By: Relevance
“…that an Asp-Asp doublet-encoding sequence is included in the consensus RT motif (as motif C) present in the catalytic subunit of eukaryotic telomerases and in the HIV-RT (16,17); furthermore, mutation of this doublet abolishes the RNA-dependent DNA polymerase activity of both telomerase and HIV-RT (16,17). Accordingly, we replaced the Asp-Asp doublets at positions 464-465 and 471-472 in the Streptomyces TopA protein with Ala-Ala doublets and, remarkably, found that the resulting protein failed to show detectable RT activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…that an Asp-Asp doublet-encoding sequence is included in the consensus RT motif (as motif C) present in the catalytic subunit of eukaryotic telomerases and in the HIV-RT (16,17); furthermore, mutation of this doublet abolishes the RNA-dependent DNA polymerase activity of both telomerase and HIV-RT (16,17). Accordingly, we replaced the Asp-Asp doublets at positions 464-465 and 471-472 in the Streptomyces TopA protein with Ala-Ala doublets and, remarkably, found that the resulting protein failed to show detectable RT activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We report here that the telomere complex of Streptomyces linear replicons also includes DNA polymerase and DNA topoisomerase proteins essential to Streptomyces propagation and, remarkably, that both of these eubacterial enzymes can function efficiently as RTs in addition to having the biochemical properties predicted from their sequences. We further show that the Streptomyces coelicolor and Streptomyces lividans TopA proteins are prototypes for a subfamily of bacterial topoisomerases whose catalytic domains contain a unique AspAsp doublet motif that is required for their RT activity and which is essential also to the RNA-dependent DNA polymerase functions of HIV RT and eukaryotic cell telomerases (16,17). (15) was amplified by using a pair of primers: 5Ј-AAACATAT-GCATCATCATCATCATCATGTGTCCGGTAGAGGAGC-GCAG-3Ј and 5Ј-GCCGTTGCCGAACAGGCTCAT-3Ј, and the amplicon was inserted into the NdeI͞EcoRI-digested pHZ1272 vector (Z. Deng, personal communication), generating plasmid pBC174.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In analyzing mutations at Tyr-115, several groups have found that the only amino acid substitution that has little deleterious effect on the enzyme is Tyr-115-Phe (7)(8)(9)(10)(11)(12)(13)(14). Substitution of Tyr-115 with polar amino acids is extremely deleterious (9)(10)(11)(12)(13) whereas substitution with hydrophobic amino acids usually has an intermediate effect (7,8,11,12,14).…”
mentioning
confidence: 99%
“…Substitution of Tyr-115 with polar amino acids is extremely deleterious (9)(10)(11)(12)(13) whereas substitution with hydrophobic amino acids usually has an intermediate effect (7,8,11,12,14). Recently, the Tyr-115-Phe mutation, along with the mutations Lys-65-Arg, Leu-74-Val, and Met-184-Val, has been detected in HIV-1 RTs resistant to the carbocyclic nucleoside analog 1592U89 (abacavir) (15,16).…”
mentioning
confidence: 99%